Let love liberate our children to learn - Hazel G. Whitters (Scottish Journal of Residential Child Care)
This article is a short reflection on an example of practice within one early years' establishment which represents the journal's special issue theme, "The extraordinary ordinary: The power of everyday care." The practice focuses upon intervention for three generations of a family. The grandmother and mother experienced adversities in childhood, and similar circumstances exist for Holly who is three years old. The emotional and physical effects of toxic stress upon learning through play are presented from Holly's perspective. The practicality of daily living for her mother, in a context of addictions, is described as a potential barrier to participation. The long-term impact of trauma upon each generation is represented by the grandmother's negative attitude to change and her inability to provide a role model for the family. The article concludes by emphasising a key aspect in the complex process of transforming research into practice in the field of child protection: Sensitive and empathic responding by a practitioner which nurtures family love, and secure attachment.